Susceptibility of muscle and visceral lipids of three sugeonfishes (naso unicornis, naso vlamigii and naso lopezi) to oxidative rancidity. - Marte, Alfredo Teofilo L. (College of Fisheries, University of the Philippines, 1993)
Muscle and visceral lipids from three species of Naso (N. unicornis, N. vlamingii, N. lopezi) were extracted and iodine, saponification and peroxide values were determined. Lipids from muscle and viscera from each species differed in all characteristics indicating differences in composition. Total lipids ranges from 0.94-2.61% for the muscle lipids and 6.34 to 18.18% for the visceral lipids. Visceral lipids have higher saponification number ranges from 107.94 to 122.58 mg K0H/kg sample while that of the visceral lipids ranges from 92.78 to 153.02-mgK0H/kg samples for the three species. Stability tests done on the muscle and visceral lipid extracts show that peroxidation rates rapidly increased up to five hours under strong aeration at 40 degree C but decreased and was low at eight hours. Visceral lipids underwent slower rates of degradation compared to muscle lipids, which may be due to the presence of antioxidants in the lipid extract. It ranges from an average rate of 1.94 meq/hr for Naso vlamingii to 4.56 meq/hr for Naso lopezi. Naso uinicornis have an intermediate rate of 2.84 meq/hrthe muscle lipids showed a more uniform peroxidation rates which ranges from 3.55 meq/hr for Naso unicornis to 4.50 meq/hrfor Naso lopezi,. Naso vlamingii have an intermediate rate of 66 meq/hr.